Measurement of fluence at the D-line fast neutron facility at iThemba LABS - Musonza, Emmanuel Tapiwa (Department of Physics, 2015)
Measurements of fluence were made for the neutron beams produced at the fast neutron beam facility of iThemba LABS, using an NE213 organic liquid scintillator detector and a 238U fission ionisation chamber. Neutron beams were produced by irradiating a 6 mm natural lithium target with pulsed proton beams obtained from the k = 200 separated sector cyclotron. Three incident proton beam energies were used in this work, namely 65.99 MeV, 99.44 MeV and 203.33 MeV. From time-of-flight measurements with the NE213 scintillator, the spectral fluence of the neutron beams was obtained. Pulse shape discrimination was used to correct for gamma ray induced signals in the NE213 detector. Simultaneous measurements of the neutron beam flux were performed at 0° and 16°. The 238U detector was used to obtain peak fluence measurements relative to the 238U(n,f) cross section.